Effects of Alloyed and Oxide Phases on Methanol Oxidation of Pt-Ru/C Nanocatalysts of the Same Particle Size - Godoi, Denis Ricardo Martins de [UNESP]; Perez, Joelma [UNESP]; Villullas, Hebe de Las Mercedes [UNESP] (Amer Chemical Soc, 2009)
In this work, methanol oxidation was studied on carbon-supported Pt-Ru nanocatalysts, where the amounts of alloyed and oxide phases were modified by heat treatments in different atmospheres. Because particle growth was avoided using, mild temperature conditions, the study reported here was conducted in the absence of particle size effects. All samples were characterized by X-ray diffraction and transmission electron microscopy. The general electrochemical behavior of the nanocatalysts was evaluated by cyclic voltammetry, and the electrocatalytic activity for the oxidation of methanol was studied in 0.5 mol L(-1) methanol acid solutions by linear potential sweeps and chronoamperometry. The results obtained clearly evidence that the presence of oxide species is necessary to enhance the electrocatalytic activity for methanol oxidation. Oxidation of adsorbed CO was also measured. Both reactions, methanol and adsorbed CO oxidation, were found to be very sensitive to the surface changes produced by the heat treatments. Interestingly, the best catalyst for methanol oxidation was not found to be the most efficient for the oxidation of adsorbed CO. Electrocatalytic activities correlate well with oxidation states and electronic properties analyzed by X-ray photoelectron spectroscopy and in situ dispersive X-ray absorption spectroscopy.